Impact of concurrent genomic alterations in epidermal growth factor receptor (EGFR)-mutated lung cancer - Gini, Beatrice (J Thorac Dis, 2020)
Comprehensive characterization of the genomic landscape of epidermal growth factor receptor (EGFR)-mutated lung cancers have identified patterns of secondary mutations beyond the primary oncogenic EGFR mutation. These include concurrent pathogenic alterations affecting p53 (60–65%), RTKs (5–10%), PIK3CA/KRAS (3–23%), Wnt (5–10%), and cell cycle (7–25%) pathways as well as transcription factors such as MYC and NKX2-1 (10–15%). The majority of these co-occurring alterations were detected or enriched in samples collected from patients at resistance to tyrosine kinase inhibitor (TKI) treatment, indicating a potential functional role in driving resistance to therapy. Of note, these co-occurring tumor genomic alterations are not necessarily mutually exclusive, and evidence suggests that multiple clonal and sub-clonal cancer cell populations can co-exist and contribute to EGFR TKI resistance. Computational tools aimed to classify, track and predict the evolution of cancer clonal populations during therapy are being investigated in pre-clinical models to guide the selection of combination therapy switching strategies that may delay the development of treatment resistance. Here we review the most frequently identified tumor genomic alterations that co-occur with mutated EGFR and the evidence that these alterations effect responsiveness to EGFR TKI treatment.